Legal Protection For Consumers Using Dentures By Dental Services - Restiana, Adevia Ayu; Purwani, Sagung Putri M. E. (Unram Law Review, 2023)
The research aims to analyse the legal protection for consumers who use prosthodontics by dental worker, and the legal authority and responsibility of dental worker (dentists) regarding the installation of false teeth (prosthodontics). The research used is normative legal research, using a statutory approach and a conceptual approach with primary legal material and secondary legal material. Legal protection for consumers regarding dental service practices has not been fully implemented in the Consumer Protection Law. The authority of dental worker (dentists) has been regulated in Minister of Health Regulation 39 of 2014. However, in practice, it is not implemented following applicable regulations. The responsibility of dental worker (dentists) for patients who use dentures (prosthodontists) is they provide pain relief medication due to the installation of dentures as well as repairing the installation of the dentures they have made. Additionally, the dental worker shall provide compensation following the applicable law.